High efficiency motors. Selection criteria (Ciencias de la Ingeniería y Aplicadas, 2021)
Considering that, of the total energy generated in the world, approximately 60% is consumed by electric motors, establishing the mandatory increase in the efficiency of these motors emerged among the most promising measures for energy saving, which has made that their selection is avant-garde, meets selection standards and parameters. This article presents selection criteria for high efficiency motors and what the advantages and complications would be when deciding the application of efficient energy use in industry.
Keywords: Engine; High efficiency; Selection